MiRNA-181d Expression Significantly Affects Treatment Responses to Carmustine Wafer Implantation. Issue 1 (26th May 2018) - Sippl, Christoph; Ketter, Ralf; Bohr, Lisa; Kim, Yoo Jin; List, Markus; Oertel, Joachim; Urbschat, Steffi
Abstract: BACKGROUND: Standard therapeutic protocols for glioblastoma, the most aggressive type of brain cancer, include surgery followed by chemoradiotherapy. Additionally, carmustine-eluting wafers can be implanted locally into the resection cavity. OBJECTIVE: To evaluate microRNA (miRNA)-181d as a prognostic marker of responses to carmustine wafer implantation. METHODS: A total of 80 glioblastoma patients (40/group) were included in a matched pair analysis. One group (carmustine wafer group) received concomitant chemoradiotherapy with carmustine wafer implantation (Stupp protocol). The second group (control group) received only concomitant chemoradiotherapy. All tumor specimens were subjected to evaluations of miRNA-181d expression, results were correlated with further individual clinical data. The Cancer Genome Atlas (TCGA) dataset of 149 patients was used as an independent cohort to validate the results. RESULTS: Patients in the carmustine wafer group with low miRNA-181d expression had significantly longer overall (hazard ratio [HR], 35.03, [95% confidence interval (CI): 3.50-350.23], P  = .002) and progression-free survival (HR, 20.23, [95% CI: 2.19-186.86], P  = .008) than patients of the same group with a high miRNA-181d expression. These correlations were not observed in the control group. The nonsignificance in the control group was confirmed in the independent TCGA dataset. The carmustine wafer group patients with low miRNA-181d expression also had a significantly longer progression-free ( P  = .049) and overall survival (OS) ( P  = .034), compared with control group patients. Gross total resection correlated significantly with longer OS ( P  = .023). CONCLUSION: MiRNA-181d expression significantly affects treatment responses to carmustine wafer implantation.